BIOCHEMICAL AND HISTOPATHOLOGICAL CHANGES OF TRADITIONAL SIDDHA FORMULATION ON CCL4 INDUCED LIVER FIBROSIS IN RATS - Manickam, Diwakar; Ramamoorthy, Sri Kamatchi Priya; Kumar, B. Santhosh; Subramaniam, Samu; Subramaniam, Shyama (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
ABSTRACT Objective: The main objective of this study is to evaluate therapeutic activity of traditional siddha formulation on CCl4 induced liver fibrosis in rats. Methods: Plant materials collected, shade dried, mixed equal proportion. This mixture was used for extract or kasayam preparation. Twenty four male Wistar albino rats were randomly divided into four groups of six rats each. The normal control group was allowed free access to food and water. Drug control group was allowed to daily intragastric administration of traditional siddha formulation 400mg per kg b.wt per day. Liver damage was performed in the remaining two groups with an i.p.injection of a 1.0 mL/kg b.wt CCl4 and olive oil (2:3 v/v) mixture, twice weekly for 8 weeks. All rats, with the exception of the injury model group, were intragastrically administered traditional siddha formulation (TSF) dosage 400 mg/ kg b.wt /day from 5th week to end of experiment of CCl4 intoxicated rats. The serum levels of hepatic markers and hydroxyproline (Hyp) in the rat livers were measured. Histopathological changes in the liver were assessed for each group using H&E staining and Masson Trichrome examination. Results: Traditional siddha formulation significantly reverse the liver function in CCl4 intoxicated rats correlate with both biochemical and histopathological changes Conclusion: Traditional siddha formulation a promising drug for treating liver fibrosis. Keywords: Traditional siddha formulation, Liver fibrosis, CCl4 and Vaithiyars